2017
DOI: 10.3389/fcimb.2017.00396
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis in Animals Due to Environmental Chemical Exposures

Abstract: The gut microbiome consists of over 103–104 microorganism inhabitants that together possess 150 times more genes that the human genome and thus should be considered an “organ” in of itself. Such communities of bacteria are in dynamic flux and susceptible to changes in host environment and body condition. In turn, gut microbiome disturbances can affect health status of the host. Gut dysbiosis might result in obesity, diabetes, gastrointestinal, immunological, and neurobehavioral disorders. Such host diseases ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
104
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(114 citation statements)
references
References 163 publications
5
104
0
2
Order By: Relevance
“…Previous studies have revealed that genetics, diet and health affect weaning weight of meat rabbits (Gomez‐Conde, et al , ; Volek, et al , ; De Blas, ; Drouilhet, et al , ; Garreau, et al , ). Recently, evidence has suggested that the gut microbiome plays a crucial role in weaning weight modulation (Rosenfeld, ; Han, et al , ; De Rodas, et al , ; Zhou, et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that genetics, diet and health affect weaning weight of meat rabbits (Gomez‐Conde, et al , ; Volek, et al , ; De Blas, ; Drouilhet, et al , ; Garreau, et al , ). Recently, evidence has suggested that the gut microbiome plays a crucial role in weaning weight modulation (Rosenfeld, ; Han, et al , ; De Rodas, et al , ; Zhou, et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, evidence has suggested that the gut microbiome plays a crucial role in weaning weight modulation (Rosenfeld, 2017;De Rodas, et al, 2018;Zhou, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such differences in microbial exposure in early development associate with different profiles of immune function (33). Furthermore, adverse postnatal environments that are often comorbid with socioeconomic risk, such as frequent antibiotic use or toxin exposure, associate with altered microbial composition and intestinal permeability (34, 35). Future work should build upon these findings to test if the microbiome may serve as a mechanism by which economic and social adversity (socioeconomic risk) influences behavioral dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…In multicellular organisms, the microbiome contributes to critical aspects of host development and physiology (1). In ecological, evolutionary and ecotoxicological research, there is growing recognition that environmental stresses imposed upon the microbiome may drive physiological responses, life-history penalties and adaptation capacity of their hosts (2), (3) 4). Consequently, coping with various environmental insults would involve both the host and its microbiome responses.…”
Section: Introductionmentioning
confidence: 99%
“…These reductions we expected would be due to reduced bacterial diversity in particular, and to some extent, an altered community composition. These hypotheses were tested by combining (1) long-term (21 d) exposure experiments with life-table analysis, (2) microbiome profiling using the next generation sequencing of 16S rRNA gene and taxonomic assignment, and (3) measurements of daphnid total antioxidant capacity, growth, and fecundity.…”
Section: Introductionmentioning
confidence: 99%